The Effects of Project-Based Learning on Social-Emotional Skills among Junior High School Students - Hadina Hadina; Mohammad Jamhari; Raya Agni; Gamar Shamdas; Bustamin Bustamin; Moh. Sabran (Equator Science Journal, 2026)
This research investigated the impact of the project-based learning (PjBL) model on the social-emotional skills. A quantitative approach with a quasi-experimental pretest-posttest control group design was utilized. The study population included all grade eight students at SMP Negeri 4 Palu during the 2025/2026 academic year. Cluster random sampling was used to select the sample, resulting in two groups: Class VIII-A (experimental group, n=27), where the PjBL model was applied, and Class VIII-B (control group, n=30), which received traditional instruction. Social-emotional skills were measured using a questionnaire that assessed the five key CASEL competencies and demonstrated high reliability (α = 0.87). Data analysis involved the Shapiro-Wilk test for normality, Levene’s test for homogeneity, and the Mann-Whitney U test for hypothesis testing, as the data did not meet normality and homogeneity assumptions. The findings revealed a Mann-Whitney p-value of 1.000 (p > 0.05), leading to the acceptance of the null hypothesis. Therefore, it was concluded that the PjBl model did not significantly affect students’ social-emotional skills.